2012
DOI: 10.5665/sleep.1738
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Sleep-Cardiovascular System Interaction in Narcolepsy with Cataplexy: Effects of Hypocretin Deficiency in Humans

Abstract: Hypocretin deficiency in humans may couple with an altered nighttime BP regulation that can be associated with an increased cardiovascular risk. This finding may be the result not only of the hypocretinergic deficiency per se but also of the altered sleep/wake regulation characterizing NC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 39 publications
4
102
0
Order By: Relevance
“…Accordingly, autonomic dysfunctions such as pupillary abnormalities, erectile dysfunction, low body temperature, and cardiovascular abnormalities were often reported in narcoleptic patients (Plazzi et al, 2011). However, data on resting autonomic tone during wake in NC patients are conflicting: some studies found a reduced sympathetic tone (Fronczek et al, 2008) while others reported increased sympathetic activity (Grimaldi et al, 2012). This aspect is particularly relevant as elevated sympathetic activity may increase the risk of cardiovascular disorders for NC patients who already may present other cardiovascular risk factors such as obesity, diabetes, sleep apnea, and metabolic syndrome (Poli et al, 2009;Jennum et al, 2013).…”
Section: Sleep Disordersmentioning
confidence: 96%
“…Accordingly, autonomic dysfunctions such as pupillary abnormalities, erectile dysfunction, low body temperature, and cardiovascular abnormalities were often reported in narcoleptic patients (Plazzi et al, 2011). However, data on resting autonomic tone during wake in NC patients are conflicting: some studies found a reduced sympathetic tone (Fronczek et al, 2008) while others reported increased sympathetic activity (Grimaldi et al, 2012). This aspect is particularly relevant as elevated sympathetic activity may increase the risk of cardiovascular disorders for NC patients who already may present other cardiovascular risk factors such as obesity, diabetes, sleep apnea, and metabolic syndrome (Poli et al, 2009;Jennum et al, 2013).…”
Section: Sleep Disordersmentioning
confidence: 96%
“…Other studies in which heart rate variability was measured in patients with narcolepsy have demonstrated normal reduction in sympathetic outflow during sleep, but reduced parasympathetic tone during wakefulness (Ferini-Strambi et al, 1997) or enhanced sympathetic activity during orthostatic stress (Grimaldi et al, 2010b). Baseline heart rate has also been reported to be elevated in narcolepsy (Grimaldi et al, 2012; Sorensen et al, 2013). The normal responses of increased heart rate in relation to arousals from sleep and decreased blood pressure during sleep have been shown to be blunted in narcolepsy with cataplexy (Dauvilliers et al, 2012; Grimaldi et al, 2012), particularly in those patients with low or absent HCRT1, even compared to narcolepsy patients with normal HCRT1 levels (Sorensen et al, 2013).…”
Section: Overview Of Narcolepsymentioning
confidence: 98%
“…Baseline heart rate has also been reported to be elevated in narcolepsy (Grimaldi et al, 2012; Sorensen et al, 2013). The normal responses of increased heart rate in relation to arousals from sleep and decreased blood pressure during sleep have been shown to be blunted in narcolepsy with cataplexy (Dauvilliers et al, 2012; Grimaldi et al, 2012), particularly in those patients with low or absent HCRT1, even compared to narcolepsy patients with normal HCRT1 levels (Sorensen et al, 2013). Together, these results support the hypothesis that HCRT insufficiency, concomitant with altered sleep architecture, leads to increased sympathetic activation.…”
Section: Overview Of Narcolepsymentioning
confidence: 98%
“…46 This is relevant because previous work on NT1 patients found that the increase in ABP upon morning awakening was blunted in these patients compared with normal controls. 47 This difference was attributed, at least in part, to the higher occurrence of periodic leg movements during sleep and the greater sleep fragmentation before awakening in NT1 patients. 47 Blunted differences in ABP and HR between NREM sleep and wakefulness 13 and a more common non-dipping pattern of ABP 48,49 have also been reported in NT1 patients compared with control subjects.…”
Section: Changes In Abp and Hr Upon Awakening From Nrem Sleepmentioning
confidence: 99%
“…47 This difference was attributed, at least in part, to the higher occurrence of periodic leg movements during sleep and the greater sleep fragmentation before awakening in NT1 patients. 47 Blunted differences in ABP and HR between NREM sleep and wakefulness 13 and a more common non-dipping pattern of ABP 48,49 have also been reported in NT1 patients compared with control subjects. However, other studies found no significant differences in ABP during wakefulness and sleep 50 or a decrease in ABP during wakefulness 51 in NT1 patients compared with controls.…”
Section: Changes In Abp and Hr Upon Awakening From Nrem Sleepmentioning
confidence: 99%